2012
DOI: 10.1021/om300305g
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Doubly SiMe2-Bridged Bis(cyclopentadienyl) Complexes of Molybdenum and Iron Carbonyls: Competitive Ring-to-Metal Migrations of Hydrogen and SiMe2

Abstract: Reaction of the doubly bridged bis-(cyclopentadiene) (C 5 H 4 (SiMe 2 )) 2 (1) with Mo(CO) 6 in refluxing xylene gave the corresponding dinuclear molybdenum carbonyl complex [(η 5 -C 5 H 3 ) 2 (SiMe 2 ) 2 ]Mo 2 (CO) 6 (3) and the desilylated product [(η 5 -C 5 H 4 ) 2 (SiMe 2 )]Mo 2 (CO) 6 ( 6), together with the singly SiMe 2 SiMe 2 -bridged dinuclear molybdenum product [(η 5 -C 5 H 4 ) 2 (SiMe 2 SiMe 2 )]Mo 2 (CO) 6 (5) and the novel complex [(SiMe 2 )(η 5 -C 5 H 4 )Mo(CO) 3 ] 2 (4) containing two Mo−Si bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
2
0
2
Order By: Relevance
“… 10 Hydride was located from Fourier difference synthesis and positionally refined isotropically 11 Other Derivatives: Cr : 2.1603(7); 2.1618(9); 2.2515(7); 2.2847(6); 2.326­(av); 2.329­(av); 2.3398(4); 2.3458(7); 2.515(7); Mo: 2.2241(7); 2.287(1) (dble); 2.300(1) (dble); 2.3430(6); 2.3474(6); 2.471­(av); 2.4550(14); 2.4562(16); 2.480­(av); 2.480(2); 2.4883(8); 2.5125(7); 2.5135(9); 2.515(2); 2.5172(8); 2.519(4); 2.5221(9); 2.5231(19); 2.546(2); 2.5536(13); 2.554(5); 2.5552(17); 2.584(3); 2.608; 2.6178(6); 2.624(3); 2.624; 2.632; 2.634(3); 2.6491(3); 2.654; 2.6659(7); 2.6675(17); 2.9647(8); 247 3.2204(9); 3.4394(10); (last 3 are considered nonbonding). W: 2.376­(dble); 2.3760(9); 2.386; 2.4202(14) (dble); 2.4562(16); 2.471­(av); 2.4990(8); 2.5086(11); 2.5125(7); 2.5257(12); 2.5474(16) (av of 2); 2.573(4); 2.5991(13); 2.608; 2.6110(13); 2.615(2); 2.620(8); 2.625(2); 2.6399(14); 2.6512(7); 2.6778(10) …”
Section: Solid State Structuresunclassified
See 1 more Smart Citation
“… 10 Hydride was located from Fourier difference synthesis and positionally refined isotropically 11 Other Derivatives: Cr : 2.1603(7); 2.1618(9); 2.2515(7); 2.2847(6); 2.326­(av); 2.329­(av); 2.3398(4); 2.3458(7); 2.515(7); Mo: 2.2241(7); 2.287(1) (dble); 2.300(1) (dble); 2.3430(6); 2.3474(6); 2.471­(av); 2.4550(14); 2.4562(16); 2.480­(av); 2.480(2); 2.4883(8); 2.5125(7); 2.5135(9); 2.515(2); 2.5172(8); 2.519(4); 2.5221(9); 2.5231(19); 2.546(2); 2.5536(13); 2.554(5); 2.5552(17); 2.584(3); 2.608; 2.6178(6); 2.624(3); 2.624; 2.632; 2.634(3); 2.6491(3); 2.654; 2.6659(7); 2.6675(17); 2.9647(8); 247 3.2204(9); 3.4394(10); (last 3 are considered nonbonding). W: 2.376­(dble); 2.3760(9); 2.386; 2.4202(14) (dble); 2.4562(16); 2.471­(av); 2.4990(8); 2.5086(11); 2.5125(7); 2.5257(12); 2.5474(16) (av of 2); 2.573(4); 2.5991(13); 2.608; 2.6110(13); 2.615(2); 2.620(8); 2.625(2); 2.6399(14); 2.6512(7); 2.6778(10) …”
Section: Solid State Structuresunclassified
“…A methylene group bridges one of the Si–Ru bonds, and the Si···C bond distance was attributed to donation of the Si–C σ-bonding electron pair to the Ru center 2.184(2); 2.196­(av); 2.200(2); 2.2157(8); 2.229(1); 2.229(11); 2.230(2); 2.236(1); 2.237(7); 2.238; 2.2478(3); 2.246; 2.2520(9); 2.2526(9); 2.253; 2.254(1); 2.254; 2.2586(8); 2.2713(6); 2.2733(8); 2.276; 2.2816(7); 2.2852(5); 2.2859(6); 2.286; 2.2918(16); 2.2922(7); 2.2937(5); 2.2942(4); 2.2949(7); 2.296; 172 2.297(4); 2.297(4); 2.2973(6); 2.298(7); 2.299; 2.300; 2.305(1); 2.306; 2.307; 2.308; 2.308; 2.309; 2.3101(7); 2.3104(9); 2.3106(9); 2.3109(15); 2.311; 2.313; 2.316; 2.317; 2.318; 2.3186(15); 2.319; 2.320; 2.322; 2.322; 2.325; 2.326(5); 2.327; 2.328; 2.3234(15); 2.3245(7); 2.3249(15); 2.329; 2.3245(7); 2.3249(15); 2.3249(5); 195 2.3261(15); 3.265(5); 2.3274(17); 2.328; 2.3291(14); 2.3291(9); 2.341; 2.354; 2.3300(14); 2.3322(4); 2.335; 2.3350(16); 2.3354(7); 2.3354(7); 2.336; 2.3373(15); 2.3378(9); 2.3442(8); 2.3560(6); 2.3573(11);…”
Section: Solid State Structuresunclassified
“…Photolyses were conducted with a 250 W high-pressure Hg lamp with the reaction vessel in an ice–water bath. The complexes [(η 5 -C 5 H 2 R) 2 (SiMe 2 ) 2 ]M 2 (CO) 4 ( 1a – c ), [(η 5 -C 5 H 4 ) 2 (CMe 2 )]Ru 2 (CO) 4 , and [(η 5 -C 5 H 4 ) 2 (SiMe 2 )]Ru 2 (CO) 4 were prepared by literature methods.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…with transition metal carbonyls have attracted attention [1][2][3][4][5][6][7]. This research group reported a series of thermal reactions of the doubly bridged dicyclopentadienes (C 5 H 4 (X))(C 5 H 4 (Y)) (X, Y = CMe 2 , SiMe 2 , GeMe 2 , or SnMe 2 ) with M(CO) 6 (M = Mo, W), Fe(CO) 5 , and Ru 3 (CO) 12 [8][9][10][11][12][13][14][15][16]. The bridging groups in the ligands could migrate to metal in the reaction to afford different types of products.…”
Section: Introductionmentioning
confidence: 99%